Nociceptin/orphanin FQ opioid receptor (NOP) selective ligand MCOPPB links anxiolytic and senolytic effects - Raffaele, Marco; Kovacovicova, Kristina; Biagini, Tommaso; Lo Re, Oriana; Frohlich, Jan; Giallongo, Sebastiano; Nhan, James D; Giannone, Antonino Giulio; Cabibi, Daniela; Ivanov, Martin; Tonchev, Anton B; Mistrik, Martin; et al. (GeroScience, 2022)
Accumulation of senescent cells may drive age-associated alterations and pathologies. Senolytics are promising therapeutics that can preferentially eliminate senescent cells. Here, we performed a high-throughput automatized screening (HTS) of the commercial LOPAC®Pfizer library on aphidicolin-induced senescent human fibroblasts, to identify novel senolytics. We discovered the nociceptin receptor FQ opioid receptor (NOP) selective ligand 1-[1-(1-methylcyclooctyl)-4-piperidinyl]-2-[(3R)-3-piperidinyl]-1H-benzimidazole (MCOPPB, a compound previously studied as potential anxiolytic) as the best scoring hit. The ability of MCOPPB to eliminate senescent cells in in vitro models was further tested in mice and in C. elegans. MCOPPB reduced the senescence cell burden in peripheral tissues but not in the central nervous system. Mice and worms exposed to MCOPPB also exhibited locomotion and lipid storage changes. Mechanistically, MCOPPB treatment activated transcriptional networks involved in the immune responses to external stressors, implicating Toll-like receptors (TLRs). Our study uncovers MCOPPB as a NOP ligand that, apart from anxiolytic effects, also shows tissue-specific senolytic effects.
Keywords: Narcotic Antagonists; Senolytic; receptory opiátové; Ligands; Humans; Opioid Peptides; ligandy; Senescence; stárnutí buněk; Nociceptin; narkotika - antagonisté; NOP; rychlé screeningové testy; lidé; zvířata; myši; Caenorhabditis elegans; anxiolytika; Receptors, Opioid; Senotherapeutics; Aging; Piperidines; Mice; léky proti stárnutí; Analgesics, Opioid; Anti-Anxiety Agents; nociceptin; opioidní analgetika; opioidní peptidy; piperidiny; Animals; Cellular Senescence; High-Throughput Screening Assays